Effects of Professional Labor Support Education to Iranian Midwifery Students on Mothers' Satisfaction - Seyedeh Fatemeh Vasegh Rahimparvar; Golnar Nasehi; Zohreh khakbazan; Anooshirvan Kazemnejad (Iran University of Medical Sciences, 2018)
Background: Majority of the textbooks for undergraduate midwifery students of Iran are educational resources for obstetricians. Therefore, the topic of Professional Labor Support is not taught well to these students. This study aimed to determine the effect of Professional Labor Support education to midwifery students (based on midwifery textbooks) on satisfaction of women who gave birth under the supervision of these students. Methods: This quasi-experimental study was conducted on 70 midwifery students of a nursing and midwifery school in Iran. Students in the intervention group (n=35) were taught Professional Labor Support in physical, emotional, and informational fields based on midwifery textbooks. The control group received conventional education. The effect of Professional Labor Support education on the students was evaluated using Professional Labor Support Questionnaire (LSQ) and satisfaction of women who gave birth under the supervision of these students (measured by a modified version of LSQ). Data analysis was conducted by Chi-square, two-sample Kolmogorov-Smirnov and Independent t tests in SPSS V. 16. Results: The Professional Labor Support delivered by the midwifery students in the intervention group was significantly higher than the control group (t=-9.16, P<0.001). Similarly, the satisfaction of women who had given birth under supervision of the trained students was significantly higher than that of women who had given birth under the supervision of the control group (P<0.001). Conclusion: Professional Labor Support education based on midwifery textbooks had a positive effect on the women's satisfaction with labor support. It is suggested that textbooks for obstetricians be replaced by midwifery textbooks recommended by International Confederation of Midwives.